Cotton (Gossypium hirsutum) establishment methods based systemintensification: Effects on Bt cotton growth, weed suppression, system crop and water productivity, system-profitability and land–use efficiency in Indo– Gangetic plains region - RAJPOOT, SUDHIR K; RANA, D S; CHOUDHARY, ANIL K; PANDE, POOJA (The Indian Journal of Agricultural Sciences, 2019)
A field experiment was conducted at IARI, New Delhi during 2014-15 and 2015-16 to study the effect of Bt cotton (Gossypium hirsutum L.) establishment methods (CEMs) and planting geometry on plant growth, yield and weed suppression behaviour in Bt cotton vis-à-vis system productivity, profitability, water-productivity, production-efficiency, economic-efficiency and land use efficiency. The experiment was laid out in split-plot-design with four replications comprising two CEMs [transplanted-cotton (TPC) and direct-seeded-cotton (DSC)] and three planting geometries/plant densities [(90×60 cm (18,518 plants/ha); 75 × 45 cm (29629 plants/ha) and 60×45 cm (37,037 plants/ha)] and four cropping systems viz. TPC−wheat−mungbean; TPC−onion−fodder cowpea + maize; DSC−wheat; and DSC−onion cropping system under above two CEMs. Among CEMs, the DSC-cotton resulted in higher plant growth though the seed yield and lint yield were respectively higher by ~9.54% and ~15% under TPC-cotton over DSC-cotton due to better plant stand in TPC–CEM. On an average, the significantly highest system productivity in terms of seed-cottonequivalent- yield (SCEY) was registered in TPC−wheat−mungbean/TPC−onion−fodder cowpea + maize cropping systems (mean of both systems) during 2014–15 (6.75 t/ha) and 2015–16 (6.96 t/ha), respectively. In general, the legume-intensification in TPC–based cropping systems exhibited about 25 to 27% higher system yield (SCEY) over DSC–based cropping systems. The TPC–based cropping systems exhibited additional net economic gains of ` 43000/ ha vis-à-vis higher weed suppression, system crop and water productivity, system economic-efficiency and land–use efficiency over the DSC–based systems. Likewise, planting geometry/planting density of 60 × 45 cm (37037 plants/ ha) exhibited significantly higher system productivity (SCEY) (6.58 t/ha), system net returns (` 178450/ha), system water-productivity and system economic-efficiency over other two planting geometries viz. 75 × 45 cm and 90 × 60 cm. In nutshell, system-intensification through transplanted Bt-cotton based cropping systems (TPC−wheat−mungbean/ TPC−onion−fodder cowpea + maize) and planting geometry/planting density of 60 × 45 cm (37037 plants/ha) led to higher weed suppression, system productivity, system economic-efficiency, system water-productivity and land–use efficiency in Indo–Gangetic plains region.